Numerical Study of a Left Ventricular Assist Device (LVAD) With Different Blade Heights and Tip Clearances - Abdul Kadir, Muhammad Rashidi; Abdul Aziz, Mohammad Azim; Padzillah, Mohammad Hasbullah; Harun, Mohamad Nor; Osman, Kahar; Abdul Rahim, Aizai Azan; Abdul Taib, Mohamed Ezani; Md Khudzari, Ahmad Zahran (International Journal of Integrated Engineering, 2018)
One treatment modality for heart failure is to employ a mechanical heart assist device to increase blood flow to peripheral organs. There are various kinds of axial and centrifugal type mechanical pumps available for implantation depending on patient condition. Axial pumps are smaller in size comparatively, although centrifugal pumps have the advantages of lower rotational speed as well as better maintaining any native blood flow pulsatility. This work presents the results of the numerical study of the centrifugal blood pump configured as a Left Ventricular Assist Device (LVAD). The pump design utilized standard industrial centrifugal pump design principles but applied to smaller sized blood pumps. Flow characteristics are modelled using 3-dimensional steady state models operating at design speed of 2000 rpm using Newtonian blood properties for the fluid. Two design parameters of the pump are studied, the impeller blade height and tip clearance resulting in nine model variants. Analysis includes the hydrodynamic performance of the pump and the flow characteristics in the pump. A haemolysis prediction model quantifying red blood cell stress from exposure time and shear stress was used for quantitative predictions of haemolysis within the blood pump. Blood damage estimation was calculated along each path-line and averaged to a single value. By using a ranked selection method, the model with the 15 mm blade height and 800 Âµm tip clearance was selected as the preferred configuration with Haemolysis Index of 0.01 mmHg, efficiency of 58% at 104 mmHg outlet pressure.